Uncovering Emerging Health Awareness Trends in Education: A Bibliometric Study - Iin Uswatun Hasanah; Jumadi Jumadi; Fauji Agusta; Rey Abraham; Siti Tsurayya Yaqutunnafis; Sri Bona Ayu (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: The study aims to examine the development of research trends related to health awareness in schools or education. Method: Data were obtained from the Scopus database and analyzed using PRISMA analysis, VOSviewer assistance, and bibliometric analysis. Results: A total of 182 relevant articles with the keywords